Influence of immersion in heat-cured resin acrylic in chitosan solution to hardness, transversal strength and modulus of elasticity - Angela Evelyna; Gabriella Jessica Suherman; Fransella Praisy Trinity Maramis; Naliani, Silvia (Indonesia Prosthodontic Association, 2024)
Background: Heat-cured acrylic resin is a commonly used material for removable denture bases but has a low mechanical strength. Heat-cured acrylic resin used as a denture base must be kept clean by immersing the denture in a cleaning agent. Denture cleaning materials on the market generally come from chemicals. Immersion of heat-cured acrylic resin as denture base in chitosan solution can inhibit the growth of Candida albicans better than oxygenizing denture cleaning solution. Biologically, chitosan is safe because it has biocompatible and biodegradable properties. Objectives: To determine the effect of immersion of heat-cured acrylic resin in chitosan solution on hardness, transverse strength, and modulus of elasticity. Materials and method: 25 acrylic resin plates measuring 65 x 10 x 2.5 mm divided into five groups. Each group was immersed in a solution of 1%, 2%, 3% chitosan, distilled water, and 1% ascorbic acid, then tested for transverse strength using the Universal Testing Machine. The values ​​of transverse strength and modulus of elasticity were calculated using the formula. Hardness test pre and post-test used 15 acrylic resin plates measuring 12mm x 12mm x 3mm were divided into five groups with each group immersed in 1%, 2%, 3% chitosan solution, distilled water, and 1% ascorbic acid. Results: Statistical analysis used one-way ANOVA for each test. The only significant difference was the modulus of elasticity between the immersion groups. The value of transverse strength, modulus of elasticity, and hardness was higher in the group with a 3% chitosan solution, with no difference statistically in transverse strength and hardness between groups. Conclusion: there was a significant difference in the effect of elastic modulus from the immersion of heat-cured acrylic resin in solution distilled water and 1% ascorbic acid as a control and 1%, 2%, and 3% chitosan solutions with ascorbic acid as a solvent